Sustainable Land Management and Strengthening Resilience of Agricultural Lands and Forests in Dominica ( PISLM -IICA) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2023)
Descripción: The Partnership Initiative for Sustainable Land Management (PISLM) has contracted IICA to support the implementation of the project entitled "Sustainable Land Management in the Commonwealth of Dominica; Strengthening the Resilience of Agricultural Land and Forests in Dominica", through a letter of agreement, for which IICA will be responsible for managing the implementation of the activities set out in the letter and delivering the corresponding outputs. This project seeks to strengthen market methodologies that support sustainable agriculture and also increase the knowledge of farmers and technicians in different agricultural technological capabilities, through certifications such as Dominica's Good Agriculture Practices (DOMGAP). Objetivo General: To increase the number of farmers utilising sustainable land management mechanisms in agriculture, improved food safety, and production quality leading to farm certification and improved market access respectively.